Ratio Decidendi of Judges toward Divorce Cases Due to Domestic Violence (KDRT) at the Jember Religious Court - Lailia Nailur Rahma Dani; Dwi Hastuti (Rechtenstudent, 2023)
The Jember Religious Court accepts quite a number of divorce cases and the divorce rate is getting higher. Until 2021, there were 1,544 divorce cases and 4,289 cases of divorce. Related to this, there are 31 cases of divorce caused by domestic violence (KDRT) in 2021. The number of divorce cases caused by domestic violence, the author is interested in analyzing how the judges consider (ratio decidendi) in deciding divorce cases due to domestic violence at the Jember Religious Court. This research is a type of empirical legal research. The results of this study are: 1. Judges' considerations in deciding divorce cases caused by domestic violence at the Jember Religious Court are in accordance with applicable legal provisions; 2. The legal consequence of the Jember Religious Court judge's decision in the divorce case against the domestic violence case was dropping raj'i divorce, with the condition that the defendant must be responsible for providing maintenance in the form of living iddah to the ex-wife and living for the children.